Why have credit variables taken centre stage in predicting systemic banking crises? - Dooneshsingh Audit; Nafis Alam (Latin American Journal of Central Banking (LAJCB), 2022)
In this paper, we investigate the growing prominence of credit in the systemic banking crisis prediction literature. Through the application of the signal extraction model and multivariate probit panel regression, we evaluate the performance of the absolute change in credit-to-GDP ratio as an early warning system indicator of systemic banking crises. The findings reveal that the accelerated financialisation of economies turns the excess supply of credit into generating conditions that increase the likelihood of a systemic banking crisis. The findings also indicate that even with persistently low and stable inflation, systemic risk could gradually accumulate through an excessive supply of credit.
Keywords: E51; E58; F30; G01; O11; O16; 330; Credit-to-GDP ratio; Systemic banking crisis; Early warning system; Financialisation